Effect of hybridization in PdAlY-(Ni/Au/Ir) metallic glasses thin films on electrical resistivity. (June 2022) - Bishara, Hanna; Kontis, P.; Dehm, Gerhard; Schneider, Jochen M.; Evertz, Simon
Abstract: Thin film metallic glasses (MGs) are promising materials for electronic applications. While the transport properties of MGs are composition dependent, the influence of hybridization on the resistivity has not been investigated systematically. We implement a correlative experimental and computational approach utilizing thin film deposition, electrical resistivity measurements, synchrotron X-ray diffraction and ab initio calculations to explore the relationship between the fraction of hybridized bonds present in PdAlY-M glasses with M =Ir, Au, Ni, where the electrical behavior is dominated by d-electrons. The strong bonds hybridization in PdAlY-Ir yields a high resistivity of 175 µΩm, while the weakly hybridized bonds in PdAlY-M MGs ( M = Au, Ni) result in lower resistivities of 114 and 92 µΩm, respectively. We propose that an increase in the amount of anti-bonding states close to the Fermi level yields an increased room temperature resistivity. Graphical abstract: Image, graphical abstract